WHEN HEALTH DOES NOT EQUATE WITH WEALTH: THE HEALTH PRACTICES AND CHALLENGES OF THE TALAANDIG TRIBE IN BUKIDNON (Proceedings of the International Conference on Future of Education, 2023)
The Talaandig indigenous group in the southern part of the Philippines has unique health practices rooted in their culture and traditions. This study explored the lived experiences and health practices of the Talaandig tribe community in Songco, Lantapan, Bukidnon. Specifically, it investigated their health practices, struggles, and challenges within the tribe. Additionally, this study designed some recommended programs to address their challenges. This paper utilized a qualitative approach, particularly the descriptive phenomenological research design. To gather the necessary data, a semi-structured one-on-one interview was conducted with the selected members of the Talaandig tribe. The interview script was content validated by a panel of experts from Central Mindanao University and Bukidnon State University. The researcher coded the interview transcripts, which the same experts validated. The study results revealed that the Talaandig tribe's health practices include feeding their children vegetables and root crops, conducting healing rituals, using herbal and traditional medicines, and consulting their elders for crucial life decisions. The Talaandig members also shared that their secondary options are visiting health centers and consulting a doctor. Regarding the struggles and challenges in their tribe, the Talaandigs shared their problems with accessing potable and affordable water, limited supply of rice as a staple food, and malnutrition among children. Based on the interview conducted, this study recommended creating livelihood programs for mothers and out-of-school youth, feeding programs for malnourished children, training on food preparation and cooking of locally available food, providing a potable yet affordable water supply, and creating health and nutrition programs for the Talaandig community in Sonco, Lantapan.
Keywords: Challenges; health practices; indigenous; Talaandig; traditions